Age Effects in a Study Abroad Context: Children and Adults Studying Abroad and at Home. Issue 1 (21st November 2012) - Llanes, Àngels; Muñoz, Carmen
<x xml:space="preserve">Abstract</x> This study examines the effects of learning context and age on second language development by comparing the language gains, measured in terms of oral and written fluency, lexical and syntactic complexity, and accuracy, experienced by four groups of learners of English: children in a study abroad setting, children in their at‐home school, adults in a study abroad setting, and adults in their at‐home university. Results show that the study abroad context was superior to the at‐home context, and more advantageous for children than for adults in comparative gains, although adults outscored children in absolute gains. The interaction between learning context and age suggests that studying abroad was particularly beneficial for children, who also had more opportunities for oral language practice.